2015
DOI: 10.3141/2476-01
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Effect of Concrete Crosstie Rail Seat Deterioration on Rail Seat Load Distribution

Abstract: One of the more critical failure modes of concrete crossties in North America is the degradation of the concrete surface at the crosstie rail seat, also known as rail seat deterioration (RSD). Loss of material beneath the rail can lead to wide gage, cant deficiency, reduced clamping force of the fastening system, and an increased risk of rail rollover. Previous research conducted at the University of Illinois at Urbana–Champaign (UIUC) identified five primary failure mechanisms associated with RSD: abrasion, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…While rail seat pressures were not directly measured, the agreement between in-track testing data and simulation results suggests the model could be used to estimate maximum rail seat pressures for various track conditions (Figures 7 and 8). The matrix-based tactile surface sensors technology is an applicable sensing technology that has been used for in-track measurements of component contact pressures (8)(9)(10)21). However, limitations of the technology, including cost, sensor durability, and maximum sample rate, have limited its application particularly in higher-speed, higher-frequency response situations.…”
Section: Comparisons With In-track Testing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While rail seat pressures were not directly measured, the agreement between in-track testing data and simulation results suggests the model could be used to estimate maximum rail seat pressures for various track conditions (Figures 7 and 8). The matrix-based tactile surface sensors technology is an applicable sensing technology that has been used for in-track measurements of component contact pressures (8)(9)(10)21). However, limitations of the technology, including cost, sensor durability, and maximum sample rate, have limited its application particularly in higher-speed, higher-frequency response situations.…”
Section: Comparisons With In-track Testing Resultsmentioning
confidence: 99%
“…Finite element analyses have also been conducted that considered specific fastening systems and fine-scale stress distributions on tie and fastening system components (6,7). Rapp et al (8) and Greve et al (9,10) have studied the application of matrix-based tactile surface sensors to measure pressure distributions at the rail seat area in-track under various load magnitudes and lateral to vertical (LV) force ratios. These studies have shown that higher LV ratios concentrate pressure on the outer half to one-third of the rail seat but have not documented pressures exceeding 7,000 psi.…”
mentioning
confidence: 99%
“…By Equation 1, this means that more than half of the rail seat load is concentrated in the critical area of the rail seat, indicating a severely nonuniform load confirmed by the analysis detailed in this paper. Lastly, Figure 11 also includes RSLI data from joint experimentation with TTCI examining the effect of rail seat deterioration on the rail seat load distribution [5]. This data is representative of extreme RSLI that may occur in the field as a result of 0.75 inches (19.1 mm) of RSD: at 0.0 L/V, the data shows an RSLI of 2.8 and increases to 4.1 under a 0.6 L/V force ratio.…”
Section: Rail Seat Load Index (Rsli) Design Metricmentioning
confidence: 99%
“…Therefore, researchers at UIUC have undertaken an effort to better understand the distribution of the rail seat load, the factors that affect it, and its effect on rail seat deterioration. Previous research has highlighted the effect of pad modulus, fastening system type, loading environment, and RSD on the rail seat load distribution [3,4,5]. Researchers at UIUC hope to incorporate the findings on RSD failure mechanisms with other FRA-funded research to generate a framework for the mechanistic design of concrete crossties and their fastening systems, in which components are designed from expected outputs and observed relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned studies, Greve et al. 10 also examined the effect of the rail seat deterioration itself on the rail seat load distribution. In their laboratory tests, they observed a correlation between the reduced contact area and the increased wear depth of the deteriorated rail seat with a triangular wear profile, which thus resulted in a significant increase in the load pressure on the rail seat.…”
Section: Introductionmentioning
confidence: 99%